Brain Serotonin 1A Receptor Binding as a Predictor of Treatment Outcome in Major Depressive Disorder - Miller, Jeffrey M.; Hesselgrave, Natalie; Ogden, R. Todd; Zanderigo, Francesca; Oquendo, Maria A.; Mann, J. John; Parsey, Ramin V. (Biological psychiatry (1969), 2013)
We previously reported higher serotonin 1A receptor (5-HT1A) binding in subjects with major depressive disorder (MDD) during a major depressive episode using positron emission tomography imaging with [11C]WAY-100635. 5-HT1A receptor binding is also associated with treatment outcome after nonstandardized antidepressant treatment. We examined whether pretreatment 5-HT1A binding is associated with treatment outcome following standardized escitalopram treatment in MDD. We also compared 5-HT1A binding between all MDD subjects in this cohort and a sample of healthy control subjects. Twenty-four MDD subjects in a current major depressive episode and 51 previously studied healthy control subjects underwent positron emission tomography scanning with [11C]WAY-100635, acquiring a metabolite-corrected arterial input function and free-fraction measurement to estimate 5-HT1A binding potential (BPF = Bmax/KD, where Bmax = available receptors and KD = dissociation constant). Major depressive disorder subjects then received 8 weeks of treatment with escitalopram; remission was defined as a posttreatment 24-item Hamilton Depression Rating Scale <10 and ≥50% reduction in Hamilton Depression Rating Scale. Remitters to escitalopram had 33% higher baseline 5-HT1A binding in the raphe nuclei than nonremitters (p = .047). Across 12 cortical and subcortical regions, 5-HT1A binding did not differ between remitters and nonremitters (p = .86). Serotonin 1A receptor binding was higher in MDD than control subjects across all regions (p = .0003). Remitters did not differ from nonremitters in several relevant clinical measures. Elevated 5-HT1A binding in raphe nuclei is associated with subsequent remission with the selective serotonin reuptake inhibitor escitalopram; this is consistent with data from a separate cohort receiving naturalistic antidepressant treatment. We confirmed our previous findings of higher 5-HT1A binding in current MDD compared with control subjects.